Drie probleemareas in gebed: "n Perspektiefvanuit die Nuwe Testament - Zyl, Hermie C. van (HTS teologiese studies, 2001)
Three problem areas in prayer: A perspective from the New Testament. Three problem areas that may cause prayer to be experienced as futile, are discussed. The areas are: the omniscience, will and omnipotence of God. Several texts in (primarily) the New Testament are treated. The article concludes that these areas do not lead to futility in prayer, but rather invite the believer to -through prayer - rest in the providence of God, and to share in his peculiar dealings with individual believers and the cosmos, dealings which are grounded in God's kindness.